Peran Muhammadiyah dalam Bidang Sosial dan Kesehatan Masyarakat Kini dan Nanti - Sukmawaty, Ice; Rahmat Sumawilaga, Rd. Andri; Ratri Wibowo, Neko (Masterpiece: Journal of Islamic Studies and Social Sciences, 2025)
The  aim  of  this  research  is  to  describe  the  social  and  health movements  carried  out  by  Muhammadiyah  as  a  leadingIslamic   organization   in   Indonesia.   This   research   uses   a qualitative  methodology  with  a  pushtakaan  approach.  The research  results  show  that  Muhammadiyah's  contribution  to the  social  sciences  of  Indonesian  society  is  largely  divided into   three   areas:   socialsciences,   education,   and   modern schools.   This   health   service   sector   consists   of   several hospitals,  maternity  homes,  polyclinics,  and  similar  areas  of social  assistance,  but  also  orphanages,  nursing  homes,  and other charitable assistance.